A Practical Methodology for Improving the Aging-Friendliness of Communities: Case Studies from Three U.S. Communities. Issue 1 (23rd March 2020) - Evans, Lauren; Oberlink, Mia R; Stafford, Philip B
Abstract: Background and Objectives: In this paper, we present a series of three case studies to illustrate an innovative and practical approach to improving the aging-friendliness of communities. These three communities used the AdvantAge Initiative to "listen" to the voices of older adults in their communities and to identify and prioritize aging-related issues. This approach was developed by the Center for Home Care Policy and Research at the Visiting Nurse Service of New York (VNSNY), the largest not-for-profit home health care organization in the United States, and has been implemented in over 60 communities throughout the United States. The methodology involves tools such as conceptual frameworks, survey questionnaires, focus groups, and technical assistance to help stakeholders interpret data and find solutions to identified issues. Research Design and Methods: We interviewed VNSNY program staff and community partners involved in three AdvantAge Initiative projects that commenced at varying time points: Memphis and Shelby County, Tennessee (2012); New York City's Chinatown neighborhood (2006); and the state of Indiana (2008). We also collected and reviewed secondary materials associated with these projects (e.g., meeting notes from community planning meetings, annual reports from grant recipients, press coverage). Results: In this case study, we begin by providing an overview of the AdvantAge Initiative framework and the AdvantAge Initiative key indicators. We then present a more in-depth look at the three communities and how they approached and implemented the AdvantAge Initiative. Discussion and Implications: These case studies demonstrate that this methodology may be implemented in diverse communities and geographic locations. By looking at the longer-term outcomes and by comparing the strategies employed by each community, we see that communities, regardless of size, can bring stakeholders together to promote health and implement meaningful changes that make the community a better place to live for older adults and their families.